Investigation the Correlation between Purchasing Power Parity, Per Capita Gross Domestic Product and the Price Level Indices with Panel Data Analysis: Evidence from New Zealand, USA, Germany, Canada and Turkey - Karacan, Rıdvan; Kilickan, Zisan (International Journal of Economics and Financial Issues, 2018)
Variables such as an Economy Purchasing Power Parity (PPP), per capita Real Gross Domestic Product (GDP) and Price Level Index are defined as the most important indicators of wealth. The Purchasing Power parity is a real variable. It shows the goods and services that people can buy with their existing incomes. Per capita income is obtained usually in one year period, in a country by dividing the total income to the country’s population. Price level indices are indicative of the general price profile of countries. It is suggested in the literature that per capita GDP and Price Levels are indicators that affect PPP. Acting on this assumption, It is intended to be tested the relationship between Purchasing Power Parity and Per-capita Real Gross Domestic Product and Price Level indices by using annual data from 2005-2016 year for Turkey, Canada, New Zealand, Germany and US economy. Panel Data Analysis is used for this purpose. According to the results of the research, there is no relation between PPP and Real GDP and Price Levels. Keywords: USA, Canada, Germany, Turkey, New Zealand, PPP, per capita real GDP, the Price Level Index, Panel Data JEL Classifications: C4, E01, E31 DOI: https://doi.org/10.32479/ijefi.6889